Phenalene—A New Ring-Locked Vinyl Bridge for Nonfullerene Acceptors With Enhanced Chemical and Photochemical Stabilities - Liu, Hongtao; Hsieh, Cheng-Tien; He, Yaxin; Chueh, Chu-Chen; Li, Zhong’an (Frontiers in Electronic Materials, 2022)
Currently, the two exocyclic vinyl bridges in the acceptor–donor–acceptor (A–D–A)-type nonfullerene acceptors (NFAs) have been widely recognized as one of the most vulnerable sites under external stresses. Embedding the exocyclic vinyl bridges into an aromatic ring could be a feasible solution to stabilize them. Herein, we successfully develop a phenalene-locked vinyl bridge via a titanium tetrachloride—pyridine catalytic Knoevenagel condensation, to synthesize two new A–D–A-type unfused NFAs, EH-FPCN and O-CPCN, wherein malononitrile is used as the electron-deficient terminal group while fluorene and carbazole rings are used as the electron-rich cores, respectively. These two NFAs possess wide bandgaps associated with deep energy levels, and significantly enhanced chemical and photochemical stabilities compared to the analogue molecule O-CzCN with normal exocyclic vinyl bridges. When pairing with a narrow bandgap polymer donor PTB7-Th, the fabricated EH-FPCN- and O-CPCN-based organic solar cells achieved power conversion efficiencies of 0.91% and 1.62%, respectively. The higher efficiencies for O-CPCN is attributed to its better film morphology and higher electron mobility in the blend film. Overall, this work provides a new design strategy to stabilize the vulnerable vinyl bridges of A–D–A-type NFAs.